Novel lutetium(III) phthalocyanine-coumarin dyads; synthesis, characterization, photochemical, theoretical and antioxidant properties - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT; TAŞKIN, TURGUT; SALAN, ÜMİT (ELSEVIER SCIENCE SA, 2021)
In this study, novel 7-oxy-3-ethyl-6-hexyl-4-methylcoumarin substituted lutetium(III) phthalocyanine compounds were synthesized, characterized and their photochemical, theoretical, and antioxidant properties were examined. All complexes were characterized by common spectroscopic methods such as FT-IR, UV?vis, 1H NMR, MALDI-TOF-MS and elemental analysis as well. Geometry optimization of phthalocyanine compounds was calculated in the B3LYP functional using 6-31G (d, p) + SDD basis set of the Density Functional Theory. Aggregation, singlet oxygen generation, and photodegradation behavior under light irradiation of the complexes (1?4) were investigated in dimethylformamide. The three phthalocyanine compounds (1, 2, and 4) showed a high level of singlet oxygen efficiency were compared with the unsubstituted zinc(II) and lutetium(III) phthalocyanine compounds because their quantum yield values were found to be over 0.80. The radical cation scavenging activities of the compounds 3 (120.344 mM trolox/mg) and 4 (188.733 mM trolox/mg) are quite remarkable in 2,2?-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid analysis according to butylated hydroxyanisole (52.63 mM trolox/mg).
Keywords: Coumarin; Phthalocyanine; Antioxidant activity; PDT; DFT; WARFARIN COUMADIN SODIUM; PHOTODYNAMIC THERAPY; ACETATE PHTHALOCYANINES; OXIDATIVE STRESS; ZINC(II); PHOTOSENSITIZERS